2012
DOI: 10.2151/sola.2012-007
|View full text |Cite
|
Sign up to set email alerts
|

Observed Effect of Mesoscale Vertical Vorticity on Rotation Sense of Dust Devil-Like Vortices in an Urban Area

Abstract: Dust devil-like vortices were detected by a three-dimensional scanning coherent Doppler lidar (3D-CDL) in an urban area of Sapporo, Japan, from April 2005 to July 2007. A total of 57 strong, dust devil-like vortices with vertical vorticity exceeding 0.1 s −1 were detected in 8 days of the observation period and were associated with a convective cell (fish net) pattern of wind fields detected by the 3D-CDL. The observed vortices had both rotation senses for 7 days. However, all of 7 dust devil-like vortices wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…hurricanes) to rotate either clockwise or anticlockwise depending on the hemisphere, for dust devil-sized vortices no preferred sense of rotation has generally been observed and only a tiny impact on sense of rotation is predicted by Large Eddy Simulation modeling (Ito et al 2011). However, in situations where the mesoscale circulation is cyclonic or anticyclonic due to local weather patterns, dust devilsized vortices are predicted -and have been observed -to share the same sense of rotation (Ito et al 2011;Fujiwara et al 2012).…”
Section: Windmentioning
confidence: 99%
“…hurricanes) to rotate either clockwise or anticlockwise depending on the hemisphere, for dust devil-sized vortices no preferred sense of rotation has generally been observed and only a tiny impact on sense of rotation is predicted by Large Eddy Simulation modeling (Ito et al 2011). However, in situations where the mesoscale circulation is cyclonic or anticyclonic due to local weather patterns, dust devilsized vortices are predicted -and have been observed -to share the same sense of rotation (Ito et al 2011;Fujiwara et al 2012).…”
Section: Windmentioning
confidence: 99%
“…Inoue et al (2011) successfully detected vortices such as tornados and mesocyclones, although not dust devils, during a winter storm event with the use of a low-level scanning X-band Doppler radar. Fujiwara et al (2011Fujiwara et al ( , 2012 used a three-dimensional scanning Doppler lidar to detect dust-devil-like vortices that develop in the daytime under fair-weather convective conditions over an urban area. They revealed that invisible dust devils frequently occur from long-term observations.…”
Section: Japanmentioning
confidence: 99%